2016
DOI: 10.1128/jvi.01451-16
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of BST-2/Tetherin Is a Conserved Function of the Env Glycoprotein of Primary HIV-2 Isolates

Abstract: Although HIV-2 does not encode a vpu gene, the ability to antagonize bone marrow stromal antigen 2 (BST-2) is conserved in some HIV-2 isolates, where it is controlled by the Env glycoprotein. We previously reported that a single-amino-acid difference between the laboratory-adapted ROD10 and ROD14 Envs controlled the enhancement of virus release (referred to here as Vpulike) activity. Here, we investigated how conserved the Vpu-like activity is in primary HIV-2 isolates. We found that half of the 34 tested prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…Several studies have mapped residues in HIV-2 group A Env proteins that are essential for efficient counteraction of human tetherin. These comprise a tyrosinebased endocytosis motif in the cytoplasmic domain, as well as several residues in the extracellular domain (i.e., K422, I568, A598, and N659) (36,38,66,67,80,81). Most of them, including N659, which is required for direct interaction of Env with human tetherin (67), are already present in SIVsmm Envs and conserved among different groups of HIV-2.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have mapped residues in HIV-2 group A Env proteins that are essential for efficient counteraction of human tetherin. These comprise a tyrosinebased endocytosis motif in the cytoplasmic domain, as well as several residues in the extracellular domain (i.e., K422, I568, A598, and N659) (36,38,66,67,80,81). Most of them, including N659, which is required for direct interaction of Env with human tetherin (67), are already present in SIVsmm Envs and conserved among different groups of HIV-2.…”
Section: Discussionmentioning
confidence: 99%
“…This is even more surprising as inactive Env proteins may act in a transdominant manner and prevent tetherin counteraction by otherwise active Env proteins (66). Notably, however, a previous study showed that only about 50% of all primary HIV-2 group A isolates encode an Env protein that antagonizes this restriction factor (38). Thus, although Env-mediated anti-tetherin activity can be found in different groups of HIV-2, it may be less conserved than Vpu-mediated tetherin counteraction in HIV-1 group M. One likely explanation is the accessibility and antigenicity of the viral envelope protein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations